Tuberous sclerosis. - Miteva, L.; Trashlieva, L. (European Journal of Pediatric Dermatology, 2002)
A case of tuberous sclerosis in a 7-year-old boy is reported. The patient had angiofibromas, hypomelanotic macules, epilepsy, mental retardation and CT evidence of multiple, ventricular calcific densities in the brain. We discuss the skin manifestations in children with tuberous sclerosis and their significance in the early diagnosis of the disease.